2020
DOI: 10.3390/ijms21031124
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Plant Chemical Biology of Jasmonates

Abstract: Lipid-derived plant hormone jasmonates are implicated in plant growth, reproductive performance, senescence, secondary metabolite productions, and defense against both necrotrophic pathogens and feeding insects. A major jasmonate is (+)-7-iso-jasmonoyl-l-isoleucine (JA-Ile), which is perceived by the unique COI1-JAZ coreceptor system. Recent advances in plant chemical biology have greatly informed the bioscience of jasmonate, including the development of chemical tools such as the antagonist COR-MO; the agonis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 85 publications
(93 reference statements)
0
17
1
Order By: Relevance
“…In response to the invasion of necrotic pathogens, jasmonic acid is (+)-7-isojasmone-1-isoleucine (JA-Ile), which can be sensed through the COI1-JAZ co-receptor system in the disease-resistant response [36]. Although we did not observe that JA-Ile was inhibited at 24hpi, it was significantly inhibited at 36hpi and 48hpi.…”
Section: Discussioncontrasting
confidence: 56%
“…In response to the invasion of necrotic pathogens, jasmonic acid is (+)-7-isojasmone-1-isoleucine (JA-Ile), which can be sensed through the COI1-JAZ co-receptor system in the disease-resistant response [36]. Although we did not observe that JA-Ile was inhibited at 24hpi, it was significantly inhibited at 36hpi and 48hpi.…”
Section: Discussioncontrasting
confidence: 56%
“…The perception mechanism of the JA-signaling pathway is well known in Arabidopsis, which is activated through the formation of the COI1-JAZ complex mediated by the JA-Ile ligand 11,12,30 . COI1 co-receptor acts like a primary receptor recognizing the ligand JA-Ile and then binding to JAZ repressors 11,12 , which are degraded by 26S proteasome 9,10 .…”
Section: Discussionmentioning
confidence: 99%
“…Besides Arabidopsis and the bryophyte Marchantia polymorpha 29 , understanding of the molecular mechanisms involved in JA-Ile perception and the activation of the JA-signaling pathway in other plant species is very limited 30 . Previously, we have described the high conservation of COI1 and JAZ proteins in F. vesca suggesting a critical role for the JA-signaling pathway in this species 20,28 . This study aimed was to evaluate if the new degron IPMQRK found in F. vesca JAZ1 is conserved in F. × ananassa and the Rosaceae family and if it can interact with the corresponding COI1 protein in the presence of COR.…”
mentioning
confidence: 99%
“…(+)-Jasmonoyl- l -isoleucine (JA-Ile, 1 ) is a lipid-derived plant phytohormone, implicated in the regulation of plant growth, fertility, and defense against pathogens and insects 1 3 . JA-Ile-mediated signal transduction depends on the COI1-JAZ co-receptor system, composed of an F-box protein CORONATINE INSENSITIVE 1 (COI1) and JASMONATE ZIM-DOMAIN (JAZ) repressor protein 4 6 .…”
Section: Introductionmentioning
confidence: 99%